2014
DOI: 10.1158/2326-6066.cir-13-0211
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of MAGE-A Expression in Resected Non–Small Cell Lung Cancer in Relation to Clinicopathologic Features and Mutational Status of EGFR and KRAS

Abstract: Non-small cell lung cancer (NSCLC) is a major public health problem, accounting for more cancer-related deaths than any other cancer. Both immunotherapy, based on the expression of tumor-specific antigens, and targeted therapy, based on the presence of oncogenic mutations, are under development for NSCLC. In this study, we analyzed the expression of MAGE-A, a cancer-testis antigen, in tumors from a cohort of patients with resected NSCLC with respect to their clinicopathologic characteristics and their mutation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
0
17
2
Order By: Relevance
“…The expression of MAGE-A and other CT antigens has been evaluated as a biomarker in several studies; however, data on the prognostic relevance is sparse. Although expression of MAGE-A genes in lung cancer tissue has been reported as marker of poor prognosis in adenocarcinoma (21) and squamous tumors (22), no correlations were found between MAGE-A expression in blood or bone marrow and tumor histology in the current study. Although MAGE-A expression in our study serves only as a marker for the presence of MRD in blood or bone marrow and as a quantitative measure of the systemic tumor load, its expression in the primary tumor may be indicative of a more aggressive quality of the disease as such (23).…”
Section: Discussioncontrasting
confidence: 82%
“…The expression of MAGE-A and other CT antigens has been evaluated as a biomarker in several studies; however, data on the prognostic relevance is sparse. Although expression of MAGE-A genes in lung cancer tissue has been reported as marker of poor prognosis in adenocarcinoma (21) and squamous tumors (22), no correlations were found between MAGE-A expression in blood or bone marrow and tumor histology in the current study. Although MAGE-A expression in our study serves only as a marker for the presence of MRD in blood or bone marrow and as a quantitative measure of the systemic tumor load, its expression in the primary tumor may be indicative of a more aggressive quality of the disease as such (23).…”
Section: Discussioncontrasting
confidence: 82%
“…However, we did not analyse expression significance due to the limited case number. In other studies, no significant difference in survival between patients with MAGE-A-expressing or MAGE-A-negative tumours was found in lung squamous-cell carcinoma, while for LAC and other histological subtypes, survival was significantly worse for patients with MAGE-A expression,39 which indicated MAGE-A expression might be more important for the prognosis of patients with LAC.…”
Section: Discussionmentioning
confidence: 75%
“…Although EGFR mutation is more closely correlated with tyrosine kinase inhibitor (TKI) therapy than EGFR amplification, it has been reported that EGFR amplification occurs frequently in patients with LAC harbouring EGFR-activating mutations, and could serve as an indicator for better response to EGFR-TKI treatment 38. Other studies also revealed that the presence of EGFR mutation did not affect the survival of patients with NSCLC, and MAGE-A expression was not significantly different in tumours with wild type EGFR or mutated EGFR which could be selected for immunotherapy, and in the latter case in combination with TKIs 39. Interestingly, in our present study, MAGE-A expression can affect the overall survival of patients with LAC without EGFR amplification or without ALK rearrangements, but does not affect the survival of patients with EGFR amplification or with ALK rearrangements.…”
Section: Discussionmentioning
confidence: 98%
“…Again this is in line with results from previous studies that have reported more frequent spontaneous serological responses to NY-ESO-1 in SCC than in adenocarcinoma [ 21 ]. Similar to NY-ESO-1, we have recently reported that the MAGE-A antigens, that also belong to the CTA group, were more frequently expressed in SCC, as compared to adenocarcinoma [ 22 ]. Together, our findings confirm XAGE-1b immunogenicity in lung adenocarcinoma, highlighting the importance of this CTA as a promising target for immunotherapy against this tumor subtype.…”
Section: Discussionmentioning
confidence: 99%